If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9(2s+1)-3s=4s-6
We move all terms to the left:
9(2s+1)-3s-(4s-6)=0
We add all the numbers together, and all the variables
-3s+9(2s+1)-(4s-6)=0
We multiply parentheses
-3s+18s-(4s-6)+9=0
We get rid of parentheses
-3s+18s-4s+6+9=0
We add all the numbers together, and all the variables
11s+15=0
We move all terms containing s to the left, all other terms to the right
11s=-15
s=-15/11
s=-1+4/11
| n+6=12-n^2 | | 24.95m(49.95)=424.20 | | 97=4x+17 | | 6z-27=2 | | 28=v/5-14 | | 8k-3=21 | | 28=v5-14 | | 3x.12=4x.7 | | 3x+4=x+0 | | F(x)=2x2-5x-12 | | 5x-8=2+6 | | 10x-19+15x-59=180 | | 3x+4=-2(4x-5) | | 7q−7q=0 | | -8b=9−7b | | 3m+4=5(m-2) | | 57974=1.2x+x | | -85=-5(4-4x)-5 | | x-3(x+6)=46 | | 7w+8=6w+1 | | 1⁄4(20-4a)=6-a | | 6(6x+1)=222 | | 7x+12÷4=4×+3 | | 3-4x=-20 | | 3−4x=−20 | | 4x+10=3-1 | | 14x2-10=8x2+360 | | —3x-14=7 | | 54=4y+17 | | 4/k=3=8/4 | | 4s-(3s-2)=34 | | 4(-5-2a)=-68 |